PENGARUH MODEL QUANTUM LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IV SDN RAWALELE DAWUAN - Muhamad Faizal; Nurlaela; Lili Herawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This research is motivated by the low ability of mathematical understanding of grade IV students. The purpose of this research is to find out how far the influence of the quantum learning model has on the ability to understand mathematics. The samples in this study were 19 students from Rawalele Elementary School, class IV A, and 19 students from class IV B. The data in this study were collected through written tests and documentation. The method used is a quasi-experimental research design using The Nonequivalent Pretest Posttest Control Group Design. Based on the processing and analysis of research data, namely: (1) The quantum learning model can improve students' mathematical understanding abilities in the experimental class by using the quantum learning model and the control class with conventional models in class IV SDN Rawalele. Experimental class students (using the quantum learning model) have an average N-Gain of 0.57, whereas with the criteria of